Managing power conflict spillover in Straits of Malacca and Singapore - Abdul Rahman Yaacob (2023)
While ASEAN member states have strategic reasons not to choose sides in the US-China rivalry, it is judicious to acknowledge that neutrality may not protect them from the fallout of military conflict in the Taiwan Strait or South China Sea. The elephant in the room is the possible spillover of such conflict to the Straits of Malacca and Singapore (SOMS).